Study on the Mechanism of Aconiti Lateralis Radix Praeparata and Descurainiae Semen Lepidii Semen Herb Pairs Against Heart Failure Based on UPLC-Q TOF MSE Combined with Network Pharmacology - Jian-nan HU; Jing-ye GU; Yao DUAN; Bo PANG; Jia-ning LIU; Qiu-lu ZHAO; Zhe LIN; Fei ZHENG; Zi-feng PI; Hao YUE (Zhipu Xuebao)
The ultra-high performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q TOF MSE) technology with UNIFI software was used to analyze and identify the chemical compositions of Aconiti Lateralis Radix Praeparata (FZ) and Descurainiae Semen Lepidii Semen (TLZ) herb pairs (FZ-TLZ). The UPLC separation was performed on a Waters ACQUITY UPLC BEH C18 column (1.7 μm×2.1 mm×150 mm), and the column temperature was 30 ℃, the injection volume was 2 μL. The mobile phase was consisted of 0.1% formic acid acetonitrile (A) and 0.1% formic acid aqueous solution (B) with the flow rate of 0.2 mL/min. UPLC-Q TOF MSE was used to collect mass spectrum data under positive and negative ion modes. Then, the precise relative molecular mass and tandem mass spectrum information of the compounds were analyzed by UNIFI software. Combined with the mass spectrum information of standard and relevant references, a total of 142 compounds are identified from water extraction of FZ-TLZ, in addition to 3 common components, 96 components are identified in FZ, and 43 components are identified in TLZ, the identified compounds are mainly alkaloids in FZ and flavonoids in TLZ. On this basis, the mechanism and active components of FZ-TLZ in treating heart failure were studied by network pharmacology technology. Using these components as candidate compounds, potential targets for active ingredients and heart failure targets were identified using databases, such as TCMSP, SwissADME, DisGeNET, Drugbank, OMIM, TTD, TTD, and GeneCards. A total of 99 active ingredients are screened, involving 133 intersecting targets. Protein-protein interaction network was performed using the STRING database. The key network of “drug-component-target” was constructed using Cytoscape software, and 10 key targets (BCL2, IL6, STAT3, CASP3, PPARG, ESR1, EGFR, AKT1, MMP9, PTGS2) are screened using the CytoHubba plugin. Using topological parameters, 19 key active compounds are screened, including flavonoids (such as Karanjin, Kaempferol, Isohamnetin), alkaloids (such as ignavine, Deltoin) and andrographolide compounds. The DAVID database was used to predict the intersection target anti heart failure pathway, which are mainly involved in the regulation of AGE-RAGE signaling pathway in diabetic complications, EGFR tyrosine kinase inhibitor resistance and HIF-1 signaling pathway. This study not only provides data support for comprehensive understanding of the chemical composition of the compatibility of FZ and TLZ, but also is a preliminary research basis for clarifying the potential mechanism of FZ and TLZ in treating heart failure.